PALAEOENVIRONMENTAL AND PALAEOCLIMATIC APPROACH TO THE LATE PLEISTOCENE SITE OF ARTAZU VII (ARRASATE, NORTHERN IBERIAN PENINSULA) USING SMALL VERTEBRATES (Ameghiniana, 2017)
Artazu VII site (Arrasate, northern Iberian Peninsula) is a fossiliferous deposit accidentally discovered at the Kobate Quarry in 2012. During the next year, all the vertebrate remains attributed to the late Pleistocene (~ 93 ka) were recovered in an emergency excavation project. Here we describe, for the first time, the small vertebrate assemblage (amphibians, reptiles and small mammals) recovered at the site and the environmental and climatic results estimated from the palaeoecological affinities of the studied taxa. More than 50,000 microvertebrate elements were recovered, comprising 24 taxa and belonging seven to the Order Rodentia, five to Order Eulipotyphla, one to Order Chiroptera, seven to Order Anura and four to Order Squamata. This assemblage, measured in terms of relative abundance, and taking into account their environmental attributions, has been used to reconstruct the palaeoenvironmental and palaeoclimatic conditions in all recovered samples. In this way, we have divided the stratigraphic sequence in three different phases. Although the presence of woodland mass is presented along all the sequence, growth and reduction changes can be observed. Thus, the stratigraphic sequence begins with a landscape by open spaces. As we move forward to the top of the stratigraphic column, woodland development increases, and is in the second phase where it reaches his maximum greatest development. Finally, wood environment descends again, reaching similar values as the beginning. These forestry biotopes were related to temperate and humid conditions, comparable to the nowadays landscape. Besides, the existence of a watercourse nearby the site has been concluded.